Persepsi tokoh p0litik terhadap model pemilukada gubernur - Nugraha, Fajar (Jurnal Civics: Media Kajian Kewarganegaraan, 2017)
the conduction of election was aimed at electing people and local representatives as well as forming democratic, strong, and legitimate  government in order to pursuit national goals based on Indonesian Constitution (UUDNRI 1945). Related to general election, there was a discourse on the model of governor election. The first, governor should elected by local (provincial) council. Second model will be direct election. The third, the governor should be assigned by President. It was a case study with qualitative approach. Based on the field result, it was perceived that the ideal type of choosing governor was direct election model. It was believed that it would trigger or stimulate a democratic local government and people-oriented development, throw away political partai oligarki. It was also in accordance to public participation on decision making.